Septic arthritis of shoeulder caused by Streptococcus pneumoniae serotype 23F in a female infant. Report of a case - Flores Nava Gerardo; Hernández Delgado Lorena; Flores Rangel José Luis (Instituto Nacional de Pediatría, 2014)
We present the case of a female infant previously vaccinated against Streptococcus pneumoniae who developed a septic arthritis in the right shoulder. An artrothomy was performed. The culture of the sy- novial fluid was positive for serotype 23F Streptococcus pneumonia.